The impact of inflammation on Resistin, IL-6 and CRP in Acute Myocardial Infarction Patients. - Ibrahim, Ammal E.; EL-Yassin, Hadef D.; Sachit AL-Janabi, Hamid K. (Journal of the Faculty of Medicine Baghdad, 2011)
Background: Inflammation contributes across the spectrum of cardiovascular disease, including the earliest steps in atherogenesis. Myocardial Infarction (MI) is most commonly due to occlusion (blockage) of a coronary artery following the rupture of a vulnerable atherosclerotic plaque. It has been suggested that the adipose tissue may play an important role in mediating this chronic inflammatory process, human resistin, is a 12.5-kDa protein, it found in the inflammatory zone. Interleukin-6 (IL-6) is a pro-inflammatory cytokine, it secreted by T cells and macrophages to stimulate immune response. C-reactive protein (CRP) is a protein found in the blood, the levels of CRP rise in response to inflammation.Objective: to determine the role of Resistin in Acute myocardial infarction patients and its effects on IL-6 and CRP.Patients and Methods: The study included 50 patients with Acute Myocardial Infarction and 40 healthy subject as control, levels of resistin, Interleukin-6 (IL-6) and CRP were measured.Results: The levels of resistin, IL-6 and CRP were significantly elevated with (p